2021
DOI: 10.1002/adma.202104410
|View full text |Cite
|
Sign up to set email alerts
|

Congener‐Induced Sulfur‐Related Metabolism Interference Therapy Promoted by Photothermal Sensitization for Combating Bacteria

Abstract: of biosynthesis, energy conversion, life activities, and stress resistance. [1] As prokaryotes facing environment independently, pathogen bacteria exhibit stronger metabolic homeostasis and thus achieve stronger stress resistance than human cells, allowing them causing persistent harm to human hosts. [2,3] In implantassociated infection (IAI) conditions, the intervention of biofilm, known as bacteria communities, enables bacteria to achieve better metabolic homeostasis and stronger antimicrobial resistance, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…171 Recently, it has been confirmed that hydrogels in combination with PTT have gradually served as a strategy for averting bacterial infection. 172 Wu et al imbedded 125 I-labeled RGDY peptide-modified gold nanorods into a polyethylene glycol acrylate alginate DN hydrogel, which can obliterate pathogenic bacteria to overcome wound infection and keep cancer from recurring with the synergistic interaction of brachytherapy and PTT (Fig. 5B).…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…171 Recently, it has been confirmed that hydrogels in combination with PTT have gradually served as a strategy for averting bacterial infection. 172 Wu et al imbedded 125 I-labeled RGDY peptide-modified gold nanorods into a polyethylene glycol acrylate alginate DN hydrogel, which can obliterate pathogenic bacteria to overcome wound infection and keep cancer from recurring with the synergistic interaction of brachytherapy and PTT (Fig. 5B).…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Typically, bacteria can stand higher temperature than cells, and thus killing bacteria with PTT brings greater damage to surrounding tissues. [29] However, low-temperature PTT is insufficient to destroy rigid biofilms due to biofilm stress response (BSR). Instead, the elevated sublethal heat induces the accumulation of heat-shock proteins (HSPs) such as groEL, which prevents misfolding and aggregation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Our previous work demonstrated that heat stress could disrupt the stable structure of biofilms and activate bacterial metabolic processes, promoting intracellular iron overload against biofilms, which builds a basis for current ion therapy. [ 11 ] Nonetheless, BBIs with their higher thermotolerance capability would consequently limit the heat‐stress‐induced ion metabolism interference. [ 12 ] Therefore, promoting the thermal sensitization of biofilm by disrupting the heat shock response (HSR) is essential for enhancing the effectiveness of the ion therapy and combatting refractory BBI.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Our previous work demonstrated that heat stress could disrupt the stable structure of biofilms and activate bacte rial metabolic processes, promoting intracellular iron overload against biofilms, which builds a basis for current ion therapy. [11] Owing to high antibiotic resistance and thermotolerance, bacterial biofilm infections (BBIs) are refractory to elimination. Iron is essential for bacterial growth and metabolism, and bacteria can thus accumulate iron from surrounding cells to maintain biofilm formation and survival.…”
Section: Introductionmentioning
confidence: 99%